MMP‐14 single‐nucleotide polymorphisms are related to steroid‐induced osteonecrosis of the femoral head in the population of northern China. Issue 2 (12th December 2018) - Qi, Yuxin; Wang, Jiaqi; Sun, Mingqi; Ma, Chao; Jin, Tianbo; Liu, Yuan; Cao, Yuju; Wang, Jianzhong
Abstract: Background: Osteonecrosis of the femoral head (ONFH) is a refractory disease which frequently occurs in young and middle‐aged people. Recent studies indicated that MMP‐14 played an important role in the development of chondrocytes, metabolism of osteoblasts as well as fate decision of hypertrophic chondrocytes. The aim of this study was to investigate the association between polymorphisms of MMP‐14 and steroid‐induced osteonecrosis of the femoral head in the Chinese population. Methods: We selected 7 SNPs (rs3751488, rs1003349, rs1042703, rs2236302, rs1042704, rs2236303, and rs2236304) on gene MMP‐14 . Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using the chi‐squared test, genetic model analysis, haplotype analysis, and stratification analysis. Results: We discovered that the genotype "G/G" of rs2236302 was associated with ONFH risk in the MMP‐14 in the codominant model (OR = 8.62, 95% CI = 1.07–69.46, p = 0.038) and recessive model (OR = 8.86, 95% CI = 1.10–71.31, p = 0.013). Conclusions: We have confirmed that the susceptive SNPs (rs2236302) of MMP‐14 from the MMPs/TIMPs system exhibit a significant association with increased risk of steroid‐induced ONFH in the population of northern China. Abstract : The aim of this study was to investigate the association between polymorphisms of MMP‐14 and steroid‐induced osteonecrosis of the femoral head in the Chinese population. We have confirmed that the susceptive SNPs (rs2236302) of MMP‐14 from the MMPs/TIMPs system exhibit a significant association with increased risk of steroid‐induced ONFH in the population of northern China.